What is the substance-based carve-out under Pillar 2? And how will it affect tax competition? - Daniel Gros (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2021)
The success of the recently agreed international tax reform hinges on a technical issue in the design of the Pillar 2 global minimum tax. Pillar 2 ensures the minimum taxation of "residual" (e.g. non-routine) profits at 15%. "Routine" profit is not subject to Pillar 2. The effects depend on which of two possible options is used: Option 1 removes the incentive to compete below a liability of 15% of residual profits and puts a floor to tax competition. Option 2 still maintains an incentive for governments to compete by reducing their taxes - possibly all the way to zero. Consequences for tax competition depend on the technical details to be revealed. Announcement containing more details of the proposal are expected shortly.
Keywords: 330